2010
DOI: 10.5688/aj740457
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Instruction on Substance Abuse and Drug Diversion

Abstract: Objectives. To develop a pilot study to assess the effectiveness of a Web-based educational module on enhancing understanding of substance abuse and drug diversion, and to assess students' abilities and confidence in applying the information. Design. A Web-based instructional module was presented to students enrolled in their second preprofessional year, and students were informed that it was part of a research study. Knowledge was tested using 10 pre-and post-module questions. Students were also presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…This study found that knowledge increased after using the application (median percent knowledge gain: 20%; p,0.0001) and that more students achieved a passing score (defined as at least 70%) on the posttest compared to the pretest (pretest pass rate: 33% vs posttest pass rate: 93%; p,0.0001). 12 Satisfaction data regarding CAI also returned varied results. With lecture capture, satisfaction data was mixed, although survey response rates were high (56-95%).…”
Section: Computer-aided Instructionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study found that knowledge increased after using the application (median percent knowledge gain: 20%; p,0.0001) and that more students achieved a passing score (defined as at least 70%) on the posttest compared to the pretest (pretest pass rate: 33% vs posttest pass rate: 93%; p,0.0001). 12 Satisfaction data regarding CAI also returned varied results. With lecture capture, satisfaction data was mixed, although survey response rates were high (56-95%).…”
Section: Computer-aided Instructionmentioning
confidence: 99%
“…Of the 7 studies, 3 employed lecture capture, 6-8 1 employed a CD-ROM, 9 1 employed an audience response system, 10 1 a learning management system, 11 and 1 used web-based instruction. 12 Assessment of the CAI tools was measured mostly by examination scores, course grades, and/or preCAI and postCAI questions. The most common method of collecting satisfaction data was a postcourse survey.…”
Section: Computer-aided Instructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within pharmacy education, online learning has proven to be an effective educational tool for a variety of topics, such as substance abuse and diversion, basic statistics, as well as proper inhaler technique [5][6][7]. Recently, a school of pharmacy employed a hybrid program when opening their satellite campus, which combined online learning with traditional face-to-face instruction.…”
Section: Introductionmentioning
confidence: 99%